Analisis Perbandingan Tinggi Badan Anak Baru Masuk Sekolah (TBABS) di Desa dan Kota - Dian Fitriyani Mosa Basa; Lewi Jutomo; Marselinus Laga Nur (Yayasan Literasi Sains Indonesia, 2025)
The nutritional status of children greatly determines the future of the next generation. However, many children in Indonesia experience nutritional problems, especially in low-income areas, which risks hampering their growth and development. Objective: This study aims to determine the determinants of height of children just entering school in villages and cities. This research used a comparative analytical design with a cross-sectional approach which was carried out in two schools respectively, namely in a village and a city, Ende Regency. The number of samples used was 76 children from class 1. Data collected included height, level of energy and protein consumption. Data analysis includes univariate analysis to describe variables and bivariate analysis to test differences. The results of statistical analysis show that there is a significant difference between the height of children in villages and cities (p = 0.000), where the average height of children in cities is higher than children in villages. Conclusion: The conclusion shows that the average height of children just entering school in villages is lower than in cities, as is the level of energy and protein consumption of children just entering school.